ANALYSIS OF TRAINING NEED ANALYSIS AT THE BOARD OFEMPLOYEE AND HUMAN RESOURCE DEVELOPMENTOF TIDORE KEPULAUAN MUNICIPALITY - Abdurrahman, Abdurrahman; Halim, Halim (Jurnal Administrasi Negara, 2017)
Abstract Education and Training are needed to address the gap between the quality of task performance and the minimum quality standards required, as well as to improve the quality of work. The objective of this study is to understand and analyze the implementation of training needs analysis for Civil Servants that was undertaken by The Board of Employee and Human Resource Development of Tidore Kepulauan Municipality. This study uses a qualitative method. Analysis Unit is 8 informants and documents obtained from BKPSDM Tidore Kepulauan Municipality namely Document of Strategic Plan, Document of Performance Accountability Report, Job Analysis Document. Data were analyzed qualitatively. The results of the study show that The Board of Employee and Human Resource Development of Tidore Kepulauan Municipality did not conduct a proper and systematic training needs analysis. The training needs identification at the organizational level is determined solely by the leader, the training needs identification at the job level merely adjusting to the education and training programs offered by the organizers and the individual level needs only decided by the leadership based on intuition and desire. Therefore, it is better to BKPSDM Tidore Kepulauan Municipality in determining which part or field in the organization that need the training done through organizational analysis process by conducting out interview, participant survey and participant satisfaction data as well as by looking at the efficiency index. Keywords: Training Needs Analysis, Human Resource Development, Tidore Kepulauan Municipality.